The feasibility of electronic payment methods as an alternative to cash in the presence of the liquidity crisis in Libya - سالم محمود عازة (Dirasat in Economics and Business, 2024)
The study aimed to identify the feasibility of electronic payment methods as a means to alleviate the liquidity crisis in Libya. The study proposes that electronic payments could serve as a viable alternative to physical currency in all types of transactions and services accessed by customers in the eastern region of Libya. To achieve this goal, and by referring to previous studies in Libya. The study distributed a questionnaire to its selected sample, collected the completed one, and subjected the collected data to statistical analysis. The results of this comprehensive investigation ultimately led to the conclusion that electronic payment methods have contributed to some extent to solving the traditional problem of liquidity shortages, especially in response to the liquidity crisis in Libya.